Role of calcium in hormone‐independent and ‐resistant breast cancer. Issue 10 (4th August 2021) - Cyrus, Kedra; Wang, Qiaochu; Sharawi, Zeina; Noguchi, Glyn; Kaushal, Mudit; Chang, Tiffany; Rydzewski, William; Yeguech, William; Gibrel, Fatima; Psaltis, John B.; Haddad, Bassem R.; Martin, Mary Beth
Abstract: Approximately one‐third of estrogen receptor (ER) positive breast tumors fail to respond to or become resistant to hormonal therapy. Although the mechanisms responsible for hormone resistance are not completely understood, resistance is associated with alterations in ERα; overexpression of proteins that interact with the receptor; and hormone‐independent activation of the receptor by growth factor signal transduction pathways. Our previous studies show that in estrogen dependent breast cancer cells, activation of the epidermal growth factor signaling pathway increases intracellular calcium which binds to and activates ERα through sites in the ligand‐binding domain of the receptor and that treatment with extracellular calcium increases the concentration of intracellular calcium which activates ERα and induces hormone‐independent cell growth. The present study asked whether overexpression of calcium channels contributes to the hormone‐independent and ‐resistant phenotype of breast cancer cells and whether clinically used calcium channel blockers reverse hormone independence and resistance. The results show that hormone‐independent and ‐resistant cells overexpress calcium channels, have high concentrations of intracellular calcium, overexpress estrogen responsive genes and, as expected, grow in the absence of estradiol and that treatment with calcium channel blockers decreased the concentration of intracellular calcium, the expression of estrogen responsive genes and cell growth. More importantly, in hormone‐resistant cells, treatment that combined a calcium channel blocker with an antiestrogen reversed resistance to the antiestrogen. Abstract : What's new? One‐third of estrogen receptor‐positive breast tumors fail to respond to or become resistant to hormonal therapy, due to mechanisms that remain to be fully understood. Here, hormone‐independent and resistant breast cancer cells were found to overexpress calcium channels. The cancer cells' high concentration of intracellular calcium, overexpression of estrogen‐responsive genes, and growth in the absence of estradiol were decreased by calcium channel blockers. In hormone‐resistant cells, treatment that combined a calcium channel blocker with an antiestrogen reversed resistance. The results suggest a potential role for calcium channel blockers in the treatment of hormone‐independent and resistant breast cancer.